ELDERLY AND ACTIVE AGING AND HEALTH - da Silva Santos, Samara; Kelly da Silva, Nathalia; Cristina Cavalcante Lucena, Cybelle; Medeiros Borburema, Myllena; Gomes De Souza Silva, Lúcia; Carolina Salustino dos Santos, Maria; Claudino do Nascimento, Nathalia (Health and Society, 2022)
Aging is part of the natural process of life, this aging relates some aspects of health indicators to the gradual aging of the population, there are more specific variables such as the degree of wealth in each country, thus concentrating a greater or lesser amount of elderly people. Reflection study, which brought together thematic content, in the year 2022, sharing knowledge and the main results about the elderly and their active aging process.